PENGARUH SERVICESCAPE DAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN DAN DAMPAKNYA TERHADAP WORD OF MOUTH: STUDI KASUS : POST SHOP COFFEE TOFEE DI KOTA BOGOR - Riani Yunita (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The increasing number of coffee shops in resto industry has brought about intensecompetition in the industry. This study aims to analyze the effect of servicescapeand service quality on customer satisfaction and word of mouth. The study adoptsa survey design. Data were collected from 100 customers Post Shop Coffee ToffeeBogor City. Data analysis employed SPSS version 26 Path analysis was employedin this study. Results indicated that in path 1, servicecape and service quality hadsignigicant effect on customer satisfaction with the former one to have sinficanteffect on satisfaction. In path 2, customer satisfaction was found to have significanteffect on word of wouth. In all, the proposed model accounted for 89.5 percent ofthe variation in word of mouth. The use of cross-sectional data makes it impossibleto study how customers’ perceptions change over time. Results from this studycould, however, help managers of Post Shop Coffee Toffee Bogor City indesigning strategies aimed at improving customer satisfaction and word of mouthin order to consolidate their market share.